Identification of Quorum Quenching Bacteria and Its Biocontrol Potential Against Soft Rot Disease Bacteria, Dickeya dadantii - Syaiful Khoiri; Tri Asmira Damayanti; Giyanto Giyanto (AGRIVITA, Journal of Agricultural Science, 2017)
Dickeya dadantii is one of newly found bacteria causing soft rot on orchids in Indonesia. Infected plants showed severe rot rapidly only in few days. An effort to control the bacteria was conducted by utilizing selected quorum quenching (QQ) inducer bacteria which produce AHL-lactonase by aiiA gene. The aims of this research were to screen and identify of quorum quenching bacteria, and also assayed their biocontrol potential ability against D. dadantii in laboratory. The screening of QQ bacteria was achieved using the anti-QS test, anti-microbial activity, and detection of aiiA gene using specific primer. The determination of the ability against D. dadantii was done using the soft rot assay on potato and orchid. Among thirty one bacteria isolates screened, four isolates (in succession namely B37, BT2, GG3, and GG6) were selected to control D. dadantii. All of these bacteria showed QQ ability to suppress the virulence of D. dadantii infection on orchids, significantly. Based on nucleotide sequences of 16S ribosomal RNA, those of bacteria isolates had the highest identity with Brevibacillus brevis, Bacillus cereus ATCC14579, Bacillus cereus ATCC14579 and Bacillus thuringiensis ATCC 10792. Brevibacillus brevis was reported for the first time as QQ bacteria in this study.